How public is public space: a cross-disciplinary study of the democratic city - Lidberg, Matilda (My University, 2021)
For decades we have been able to follow urban cities using concepts that promote commercial interests rather than public, in their fight for attention on the global market. Using terms like “branding” or “profiling”, the focus that should be on the commercialisation of public space is instead disguised as development proclaimed to make the city more “attractive”. This development however risks turning public space into private and diversity into uniformity when cities as a whole and, more specifically, public spaces are planned. Today we see the impacts and consequences of it in public space, and in the end on its democratic functions. This thesis is set around questions that discuss the gap between research done on the city by social sciences, politics, and actual planning leading to architecture that shapes public space. By using a cross-disciplinary approach architects can broaden their understanding of this relationship between public space and democracy. This thesis therefore includes studies from Sociology, Cultural Studies, Geography, and Critical theory. It is also a series of design elaborations where the theories are being tested through collages. These allow a quick look at an alternative reality of a place and ask questions though visual representation, as well as spatial analysis. In building on and collaborating with scholars from other fields, architects have a great chance to learn from and include meaningful knowledge into the practical work of architecture. This thesis argues that a cross-disciplinary approach should not only be seen as a means to interesting design but that it is also imperative to secure our public spaces as democratic agents. With awareness of the mechanisms at work in city planning on the one hand and insight in the research of other disciplines on the other, architects have a great chance to strengthen both their own role in planning, and the democratic function of public space.
Keywords: Critical theory, justice, equality, gentrification, business improvement district, class, whiteness